The Turkic runic inscriptions: the problems of dating and interpretation difficulties - K. A. Kotkoff (Nomadic Civilization: Historical Research, 2024)
It is officially believed that the ancient Turkic script, called runic for its resemblance to the Scandinavian runes, existed in the period from the VI century AD to the X century AD, after which it ceased to be used, and it was practically forgotten. The Runic script of the Turks is not a common Turkic script, since its area of distribution is limited to the Minusinsk basin, the upper reaches of the Yenisei, Altai, the upper reaches of the Orkhon River and the Tola River in Mongolia. It is also represented by Turfan manuscripts and a few monuments in the Talas River valley and in Ferghana. These monuments are not precisely dated in time, the interpretation of many of them is very difficult, and in many cases we are not dealing with full-fledged translations, but, often, with the translator’s own interpretation of the text. The good preservation of many monuments indicates their relatively late origin. Most likely, these monuments belong to the XV–XVI centuries. As for the largest group of monuments — the Yenisei and Altai, they belong to the period of existence of the tribal formation of the Yenisei Kyrgyz Khongorai of the XVI–XVII centuries, which ceased to exist in 1703, when its population was mostly forcibly resettled to Dzungaria by its ruler Tsevan-Rabdan